Leveraging half-cycle orthogonal signal generation approach for PLL-less tracking of single-phase grid parameters. (15th November 2022) - Kumar, Manish; Jarial, Raj Kumar; Verma, Anant Kumar; Subramanian, Chandrasekaran; Nath, Ravindra; Kotsampopoulos, Panos C.; Mellado, Claudio Burgos
Abstract: This article presents a fast and accurate single-phase grid voltage parameter tracking scheme under distorted grid voltage conditions. The input stage of the proposed scheme consists of a half-cycle moving-window discrete Fourier transform (HC-MWDFT) based pre-filter, whose design guidelines are discussed in the viewpoint of its stability and orthogonal signal generation. Combining a positive feed-forward comb filter and a fractional complex resonator helps to attenuate odd-order harmonics and allows fast extraction of fundamental components. Unlike the phase-locked loop (PLL) techniques, the grid frequency is indirectly estimated using a simple open-loop frequency detector. The proposed method is free from tedious controller tuning aspects and can avoid external phase/frequency feedback loops. The amplitude and phase information are adaptive to the grid frequency by employing a simple linear regression-based error correction technique. The overall efficacy of the proposed algorithm is assessed using numerical and experimental methods. Highlights: Rapid detection of the fundamental frequency, amplitude, and phase information Reinvestigation of half-cycle moving window discrete Fourier transform-OSG approach Non-adaptive pre-filter approach helps avoid the frequency feedback-loop Open-loop frequency estimator is a less complex solution then the PLLs and the FLLs Better dynamic behavior, noise rejection, and reduced number of control parameters